2015
DOI: 10.2528/pierm15021404
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling and Analysis of Through Silicon Vias (Tsvs) in High Speed Three-Dimensional System Integration

Abstract: This paper gives a comprehensive study on the modeling and design challenges of Through Silicon Vias (TSVs) in high speed three-dimensional (3D) system integration. To investigate the propagation characteristics incurred by operations within the ultra-broad band frequency range, we propose an equivalent circuit model which accounts for rough sidewall effect and high frequency effect. A closed-form expression for TSV metal oxide semiconductor (MOS) capacitance in both depletion and accumulation regions is propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This study varied both the alkyl chain linkage (ether/thioether) and linker identity (serinol/ DEA), allowing us to investigate the effects of these structural differences on membrane protein stability in detail. In previous studies, an ether linkage has been compared with an alkyl linkage, 14,16,42 but it is unusual to compare the thioether linkage with another (ether or alkyl) in the context of novel detergent structure. Due to the high hydrophobicity of the sulfur atom (vs oxygen) and relatively long C-S bond (vs C-O), the thioether linkage-bearing detergents gave lower CMCs and larger micelle sizes than the ether counterparts, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study varied both the alkyl chain linkage (ether/thioether) and linker identity (serinol/ DEA), allowing us to investigate the effects of these structural differences on membrane protein stability in detail. In previous studies, an ether linkage has been compared with an alkyl linkage, 14,16,42 but it is unusual to compare the thioether linkage with another (ether or alkyl) in the context of novel detergent structure. Due to the high hydrophobicity of the sulfur atom (vs oxygen) and relatively long C-S bond (vs C-O), the thioether linkage-bearing detergents gave lower CMCs and larger micelle sizes than the ether counterparts, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variations in alkyl chain linkage (ether/thioether) and alkyl chain length (C7/C8/C9/C10/C11) introduced here influence the hydrophile-lipophile balance (HLB) essential for detergent efficacy for protein extraction and stabilization. 12,27 Of note, the thioether linkage used for the TSM/TEM-Ts is rarely exploited in novel detergent design although some studies showed that thioether-bearing detergents [e.g., n-octyl-β-D-thioglucoside (OTG)] are superior to the ether analog (OG) in membrane protein solubilization and stabilization. 28 The new agents are efficiently prepared by four high-yielding synthetic steps: 1) dialkylation, 2) coupling to an amine-functionalized diol linker (serinol/DEA), 3) AgOTfpromoted glycosylation and 4) global deprotection of multiple benzoyl groups (Scheme 1).…”
Section: Structural and Physical Characterizations Of New Detergentsmentioning
confidence: 99%
See 1 more Smart Citation